Optimization of types and quantity of the national helicopter park as a factor of customer’s cost reduction - Yu. V. Krivolutsky (Путеводитель предпринимателя, 2022)
The article shows that the main cause, which restrains wide implementation of helicopters, is the incongruity of the current park of helicopters to the character and the high cost of the performing tasks. The solvation of the problem would be a saturation of the helicopter park by the new types of helicopters. The method of calculation of the possible reduction of exploitation expenses under optimization of helicopter types in accordance with market demand is offered. The optimization of types and quantity of helicopters park enables the customers to reduce their costs and widen the possibilities of helicopters exploitation in national economy.